2001
DOI: 10.1379/1466-1268(2001)006<0386:eishih>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases serum Hsp72 in humans

Abstract: Recent evidence suggests that heat shock proteins (Hsps) may have an important systemic role as a signal to activate the immune system. Since acute exercise is known to induce Hsp72 (the inducible form of the 70-kDa family of Hsp) in a variety of tissues including contracting skeletal muscle, we hypothesized that such exercise would result in the release of Hsp72 from stressed cells into the blood. Six humans (5 males, 1 female) ran on a treadmill for 60 minutes at a workload corresponding to 70% of their peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
207
4
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(231 citation statements)
references
References 40 publications
17
207
4
3
Order By: Relevance
“…Standard criteria for an acceptable VO 2 max test included a leveling off of VO 2 with increasing workload, a respiratory exchange ratio (RER) above 1.15 and a peak HR (Telemeter heart checker, Polar, Finland) similar to age-predicted maximal values. Both groups also underwent a dual bioelectrical impedance analysis and BMI test to determine body composition 11,12) . Forty-eight hours after the bioelectrical impedance analysis (Inbody Biospace 3.0, Korea), BMI and VO 2 max test (Minato, a baseline blood sample of 10 mL was taken.…”
Section: Methodsmentioning
confidence: 99%
“…Standard criteria for an acceptable VO 2 max test included a leveling off of VO 2 with increasing workload, a respiratory exchange ratio (RER) above 1.15 and a peak HR (Telemeter heart checker, Polar, Finland) similar to age-predicted maximal values. Both groups also underwent a dual bioelectrical impedance analysis and BMI test to determine body composition 11,12) . Forty-eight hours after the bioelectrical impedance analysis (Inbody Biospace 3.0, Korea), BMI and VO 2 max test (Minato, a baseline blood sample of 10 mL was taken.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the vast literature on intracellular Hsp70, very few studies have tested the effect of stress on extracellular Hsp70. In these instances, stressors such as surgical operations [25], intense physical exercises [15,28,85], and short-run psychological stress [16,31] were shown to induce extracellular Hsp70. An extracellular elevation of another kind of chaperon (Hsp60) was also shown to be induced by long-term psychosocial stress [46].…”
Section: Possible Role Of Salivary Hsp70 Under Stress Conditionsmentioning
confidence: 99%
“…First, the time of return to baseline value for salivary eHSP70 levels is still unclear. Previous studies showed that circulating eHSP70 increased temporarily (Fehrenbach et al 2005;Whitham et al 2006) and returned to baseline within 8 or 24 h, after intense exercise (Walsh et al 2001;Suzuki et al 2006). Although the reaction times to respond to exercise stress in circulating eHSP70 and salivary eHSP70 were different, it was assumed that exercise-induced salivary eHSP70 levels might return to baseline within 24 h. Changes in eHSP70 levels should be observed for more than 4 h or until 1 or 2 days after exercise to completely determine the changes in levels at various times until return to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…The change in salivary eHSP70 levels after exercise has not been adequately examined. Walsh et al (2001) showed that increased serum eHSP70 levels returned to baseline at 2 to 8 h after exercise. It is, therefore, possible that exercise stress might continue to have an effect on salivary eHSP70 levels for a few hours.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation